On fractional differential equations involving generalized Mittag-Leffler functions (Nonlinear Studies, 2014)
In this paper we solve generalized fractional differential equations by using the Sumudu transform. The equations solved differential equations with generalized Riemann-Liouville fractional derivative operators are very general in nature and involve wide range of fractional differential equations and their solutions in terms of various functions related to Mittag – Leffler function.